Relationship of Vitamin D Deficiency with Cervical Vertebral Maturation and Dental Age in Adolescents: A Cross-Sectional Study - Golnoosh Azarbakhsh; Parastoo Iranparvar; Azita Tehranchi; Mahkameh Moshfeghi (Hindawi Limited, 2022)
Background. Considering the high prevalence of vitamin D deficiency and its effect on growth and development, the assessment of the dental age and skeletal age with regard to vitamin D deficiency status could influence the treatment planning of growth modification treatment. This study aimed to assess the relationship between vitamin D deficiency, cervical vertebral maturation (CVM) as an indicator of skeletal age, and dental age in adolescent patients. Methods. In this cross-sectional study, the chronological age of 52 orthodontic patients aged between 10 and 14 years was recorded, and their serum level of vitamin D was determined using a radioimmunoassay test. The patients were then divided into three groups based on their serum vitamin D level: severe deficiency, moderate deficiency, and the control group with normal vitamin D. The panoramic radiographs of patients were assessed to determine their dental age using Demirjian's method. CVM was determined on lateral cephalograms using Baccetti's classification to specify the skeletal age. Data were analyzed using a t-test, linear regression, ordinal logistic regression, and Pearson's correlation coefficient (at P<0.05, confidence interval = 95%). Results. Skeletal age showed a significant difference between the group with severe vitamin D deficiency and the control group (P=0.01); however, such difference was not observed between the group with moderate vitamin D deficiency and the control group (P=0.12). Dental age was not significantly different between the groups with vitamin D deficiency and the control group (P=0.26 for severe, and P=0.39 for moderate deficiency). Conclusions. A less advanced skeletal maturation was observed in adolescents with severe vitamin D deficiency; however, dental development was not affected by this deficiency. Vitamin D status is better to be considered in decision-making for the initiation of growth modification orthodontic treatments.